2005
DOI: 10.1021/ja0550273
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Multinuclear NMR and X-ray Diffraction Studies of Uranium(VI)-Nucleotide Complexes

Abstract: The complex formation of uranium(VI) with four nucleotides, adenosine- (AMP), guanosine- (GMP), uridine- (UMP), and cytidine-monophosphate (CMP), has been studied in the alkaline pH range (8.5-12) by (1)H, (31)P, (13)C, and (17)O NMR spectroscopy, providing spectral integral, chemical shift, homo- and heteronuclear coupling, and diffusion coefficient data. We find that two and only two complexes are formed with all ligands in the investigated pH region independently of the total uranium(VI) and ligand concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…They exhibit good affinity for high valence metal ions in basic conditions (pH = 8.5-12), such as VO 2+ , UO 2 2+ , Sn 4+ , Sb 5+ , and Sb 3+ [44,45,[47][48][49].…”
Section: Structures and Properties Of Nucleotide Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…They exhibit good affinity for high valence metal ions in basic conditions (pH = 8.5-12), such as VO 2+ , UO 2 2+ , Sn 4+ , Sb 5+ , and Sb 3+ [44,45,[47][48][49].…”
Section: Structures and Properties Of Nucleotide Ligandsmentioning
confidence: 99%
“…19a) [45], which is formed via the coordination of the 5-phosphate group and 2-and 3-hydroxyl groups of the sugar unit with central ions at pH ≈ 10. The X-ray single crystal diffraction analysis showed that the crystallographic unit cell contains two symmetryindependent trinuclear U(VI)-AMP molecules (A and B) with different orientations, as well as sodium counter ions and water molecules.…”
Section: Multinuclear Complexes Of Nucleotides With High Valence Statmentioning
confidence: 99%
“…Interestingly, this is also the case for [Na(5'-dAMPH)]·6H 2 O [ 37 ] , despite the different crystal packings. In the two sodium salts of a pentamolybdate complex of 5'-AMPH [ 29 ] and an uranium(VI) complex of 5'-AMP [ 30 ] , Na + ions bind solely to the phosphate groups of nucleotide molecules in the [(Mo 5 O 15 )(5'-AMPH) 2 ] 2-fragment [ 29 ] or in the trimeric [(UO 2 ) 3 (O)(5'-AMP) 3 ] -framework [ 30 ] , forming an O(P)-Na-O(W)-Na-O(P) linkage (where O(P) and O(W) denote phosphate oxygen and water oxygen, respectively) in the former [ 29 ] or a Na-O( P) bond for each of the AMP molecules in the latter [ 30 ] . Crystal structures of fi ve (Li + , Na + , K + , Ca 2+ , and Mg 2+ ) salts of 2'-AMP are reported [ 31 ] ; results on metal complexes with a 2'-nucleotide are quite scarce, to date only [Cu(2'-GMP)(H 2 O) 3 ] is reported [ 38 ] .…”
Section: Structures Of Alkali and Alkaline Earth Metal Ion Complexesmentioning
confidence: 99%
“…Each of partially occupied six Na + ions is connected to one of the [ 30 ] phosphate oxygens in each of six AMP molecules, which adopts gg and anti conformations.…”
Section: Structures Of Alkali and Alkaline Earth Metal Ion Complexesmentioning
confidence: 99%
See 1 more Smart Citation